(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
According to the philosopher Hegel, the so-called Ethical State (as a regulator of private life and popular culture) is the main political construction and, because of this, the defense of Law is not organized as if Law prevailed over the State. As the individual is rational, the violation of the Law must be punished as if there were a rescue of the rationality debased by the offender. Furthermore, without guarantees to the Law itself – especially Human Rights –, the State would be left without adequate internal control mechanisms: a phenomenon that can be seen, in fact, both in the USA and in Iran – and in Brazil, in the fulfillment and fulfillment of Rights Humans. In this perspective, the present work aims to discuss the foundations of human and fundamental rights, their characteristics and principle, instruments and policy, aiming at their concretion. It was decided to carry out an exploratory research using bibliographical review and qualitative data analysis in order to fulfill this objective, which made it possible to infer, in the end, the greatest and best instrument of Human Rights is Human Dignity itself, which should serve as a compass for the realization of human and fundamental rights.